Evaluation of heavy metal contamination and pollution indices in soil from selected dumpsites in Kelantan, Malaysia (Journal of Tropical Resources and Sustainable Science (JTRSS), 2025)
Heavy metal contamination was one of the most important environmental issues, and the dumping of municipal waste at the dumpsites led to the contamination. Hence, this study focused on three dumpsites in Kelantan which were Beris Lalang Dumpsite, Kok Bedollah Dumpsite, and Bukit Che Ros Dumpsite. This study aimed to determine the concentration of selected heavy metals and to examine the soil quality using pollution indices. The soil samples were analysed using Atomic Absorption Spectroscopy (AAS). This study revealed the mean concentration of heavy metals in soil at Beris Lalang Dumpsite as following order, Cu (16.00 mgkg-1) > Cr (11.87 mgkg-1) > Zn (10.54 mgkg-1) > Mn (6.69 mgkg-1) > Pb (5.72 mgkg-1), while Kok Bedollah Dumpsite were Mn (64.86 mgkg-1) > Zn (31.28 mgkg-1) > Cu (18.92 mgkg-1) > Pb (18.59 mgkg-1) > Cr (3.52 mgkg-1) and Bukit Che Ros Dumpsite, were Zn (17.46 mgkg-1) > Cu (13.24 mgkg-1) > Cr (8.60 mgkg-1) > Mn (5.74 mgkg-1) > Pb (4.89 mgkg-1). Meanwhile for the pollution indices, the Igeo result showed that all stations were in class 0 except for one sampling point at Kok Bedollah Dumpsite. This is also supported by the Pollution Load Index (PLI) result for each dumpsite, which was also below 1, indicating that the areas were not polluted. If dumpsite management remains not managed correctly, this contamination may continue to have an impact on soil quality in the future. As a result, the data gained from this study was valuable in assisting authorities in managing dumpsites systematically to maintain the soil quality.
Keywords: heavy metal, dumpsite, pollution indices, geo-accumulation index, pollution load index; heavy metal; dumpsite; pollution indices; geo-accumulation index; pollution load index